Michael Vey . 5 # . Storm of lightning - Evans, Richard Paul (New York Simon Pulse, 2015)
While on their most dangerous mission so far, Michael, Taylor, Ostin, and the rest of the Electroclan discover the resistance has been compromised and their families are missing
1
Keywords: Friendship -- Juvenile fiction; Genius -- Juvenile fiction